Internationalisation and Its Implications for Intercultural Maturity among Academic Staff: A Case Study - Jamilah Mustafa (2012)
The process of internationalisation can in many ways assist staff in being interculturally matured through prolong and accumulative intercultural communication experiences. Staff may undergo a gradual transformation towards being interculturally matured – thus the emergence of an intercultural personhood. Intercultural personhood coined by Kim (2008), describes individuals who move beyond the bounds of their own cultural beings and heritage to accept both their formal cultural identity and host identity. This paper explores an internationalisation project between two universities namely Universiti Kebangsaan Malaysia (UKM) and the University of Duisburg-Essen (UDE) in Germany and how this project has internationalised staff and altogether making them more interculturally matured. The findings explain the cycle of staff who initially practice only one culture, communicates with the environment, co-evolves in the new environment thus illustrating identity changes through their live experiences to become persons with multicultural traits.